2008
DOI: 10.1007/s00120-008-1652-2
|View full text |Cite
|
Sign up to set email alerts
|

Die extendierte Sentinel-Lymphadenektomie im Rahmen der radikalen Prostatektomie?

Abstract: Extended lymph node dissection during radical prostatectomy for prostate cancer remains a disputed area. Sentinel lymph scans help identify the first lymph node stages in the lymph drainage of the prostate. This study was designed to investigate the detection rate of lymph node metastasis by extended lymph node dissection and sentinel lymph node scanning in patients undergoing radical retropubic prostatectomy (RRP) for localized prostate cancer. In this study at our department from 2005 to 2006, a total of 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Studies on SLND have reported that the combination of SLND and ePLND may improve RFS [5,6,14,28], and our results confirm this finding. Additionally, some authors have suggested a benefit in terms of RFS following the combination of RRP and ePLND [1,2,6,11,14,17].…”
Section: Discussionsupporting
confidence: 82%
“…Studies on SLND have reported that the combination of SLND and ePLND may improve RFS [5,6,14,28], and our results confirm this finding. Additionally, some authors have suggested a benefit in terms of RFS following the combination of RRP and ePLND [1,2,6,11,14,17].…”
Section: Discussionsupporting
confidence: 82%
“…In patients from high- and intermediate-risk groups the chance to detect one or more positive LNs was 30% [13]. Moreover, the number of positive LNs is an important factor for tumor-specific survival.…”
Section: Discussionmentioning
confidence: 99%